2010
DOI: 10.1126/science.1193748
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness and Safety of Tenofovir Gel, an Antiretroviral Microbicide, for the Prevention of HIV Infection in Women

Abstract: on behalf of the CAPRISA 004 Trial Group ‡ The Centre for the AIDS Program of Research in South Africa (CAPRISA) 004 trial assessed the effectiveness and safety of a 1% vaginal gel formulation of tenofovir, a nucleotide reverse transcriptase inhibitor, for the prevention of HIV acquisition in women. A double-blind, randomized controlled trial was conducted comparing tenofovir gel (n = 445 women) with placebo gel (n = 444 women) in sexually active, HIV-uninfected 18-to 40-year-old women in urban and rural KwaZu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
1,610
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,114 publications
(1,668 citation statements)
references
References 32 publications
(30 reference statements)
25
1,610
5
Order By: Relevance
“…The first is the CAPRISA 004 Phase IIb study, which showed that Tenofovir reduced HIV by 39% (Abdool Karim et al, 2010). This result could not be replicated in a phase III trial (Rees et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first is the CAPRISA 004 Phase IIb study, which showed that Tenofovir reduced HIV by 39% (Abdool Karim et al, 2010). This result could not be replicated in a phase III trial (Rees et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…So far, only two products have shown significant results in preventing HIV (Abdool Karim et al, 2010;Baeten et al, 2016;Nel et al, 2016). The first is the CAPRISA 004 Phase IIb study, which showed that Tenofovir reduced HIV by 39% (Abdool Karim et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that many studies with Truvada and preventive vaginal gels, involving thousands of women, have failed in SA and other Southern African Development Community countries. [2,3] These studies include trials such as FACTS and VOICE, [4][5][6] and it is thought that failure was due to lack of adherence and not ineffectiveness. The roll-out of Truvada therefore aims to offer protection to students at risk of HIV infection, in the hope that they will have better adherence, and has been extended to HIV-negative students across nine institutions of higher learning across SA.…”
Section: In Practicementioning
confidence: 99%
“…The successful results in the use of 'treatment as prevention' to prevent HIV among serodiscordant couples may have a role in reducing HIV transmission between sex workers and clients (Baeten & Celum 2011). Pre-exposure prophylaxis in the form of a topical vaginal microbicide has shown promise in the African context, and a successful product could empower sex workers to reduce their vulnerability to HIV (Abdool Karim, Abdool Karim, Frohlich, Grobler, Baxter, Mansoor, et al 2010). In the future, and if supported by evidence, oral pre-exposure prophylaxis may be another prevention option for HIV negative sex workers.…”
Section: Preventing Hiv Among Sex Workersmentioning
confidence: 99%